BREAKING BARRIERS IN RELIGIOUS EDUCATION: INSIGHTS FROM THE PROBING PROMPTING MODEL'S IMPLEMENTATION IN A JOMBANG SCHOOL - Azfar, Fani; Suharto, Ernaka Heri Putra (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study investigates the effectiveness of the Probing Prompting learning model in the instruction of Akidah Akhlak in class X-C at MAN 1 Jombang. Employing a qualitative descriptive approach and a case study methodology, the research examines the implementation stages, effectiveness, challenges, and specific modifications made during the application of this model. The findings demonstrate a substantial improvement in student learning outcomes, particularly in cognitive, affective, and psychomotor domains. Challenges such as students' shyness, varied public speaking skills, and feelings of saturation with extensive material were identified. However, the educator's innovative instructional strategies and modifications effectively mitigated these issues. The study concludes that the Probing Prompting model, which focuses on in-depth inquiry and active student engagement, significantly enhances the learning environment, improving overall educational outcomes in Akidah Akhlak instruction. These results underscore the model's potential applicability across various subjects and educational contexts.